Selection of Notification Based on Priority Scale with Fuzzy Algorithm - Faisal Riftiarrasyid , Mohammad; Nur Diana, Sherli; Istiqomah, Aulia; Ratna Sari, Sumiati (IJDASEA (International Journal of Data Science, Engineering, and Analytics), 2021)
Notification is one method that works as a marker that there is information waiting to be read. But along with the times, notifications are increasingly filled with information that is considered less important for device users. So there needs to be a breakthrough to overcome this. This study aims to design a system that can help users to sort out notifications that are considered important and not. It is proven that the system can sort notifications based on the given metrics.